Faktor-Faktor Yang Berhubungan Dengan Tingkat Keracunan Pestisida Pada Petani Sayuran Di Desa Sambirejo Kabupaten Rejang Lebong - Widada, Agus; Mualim, Mualim; Gazali, Moh. (LPPM STIKES BHAKTI HUSADA BENGKULU, 2022)
Indonesia is a country whose livelihoods are mostly farmers, and is also known as an agricultural country. In Indonesia, many people make agriculture their main source of income. The method used by farmers to maintain their agricultural products is by using chemicals, namely pesticides. This pesticide serves to kill plant pests in prolonging their survival. Pesticide poisoning is caused by direct exposure (exposure) to pesticides (inhaling, splashing, or touching pesticide residues). The World Health Organization (WHO) and the United Nations Environment Program (UNEP) are the Environmental Programs within the United Nations (UN) estimating that there have been 1-5 million cases of pesticide poisoning among workers in developing countries (Alsuhendra and Ridawati, 2013). The type of research used in this research is cross-sectional, which is easy to do, and suitable for studying the relationship between risk factors and certain diseases or health status. The population and sample of this study were all groups of vegetable farmers in Sambirejo Village, Rejang Lebong Regency, 100 farmers were taken by random sampling. This analysis technique was carried out bivariate and univariate using chi-square statistical test. The results showed that there was a relationship between working period (p = 0.001), duration of spraying (p = 0.001), pesticide dose (p = 0.000), and completeness of PPE (p = 0.001) with the level of pesticide poisoning in vegetable farmers in Sambirejo Village, Selupu Rejang District. Rejang Lebong Regency. Suggestions for further researchers can develop research by adding parameters for checking pesticides both in vegetables and in the agricultural environment and inspection methods using other methods. Keywords: Cholinesterase, Working Period, Spraying Time, Pesticide Dosageand Complete Personal Protective Equipment